Endolymphatic sac tumour: exploring the role of CT and MRI features in the diagnosis of 22 cases. Issue 8 (August 2022) - Geng, Y.; Gu, X.; Lin, M.; Chen, W.; Tang, Z.; Sha, Y.; Song, Y.
Abstract : AIM: To explore the role of imaging features in the diagnosis of endolymphatic sac tumour (ELST). MATERIALS AND METHODS: Twenty-two patients with ELST confirmed at histopathology were included in this retrospective study. All patients underwent computed tomography (CT) and magnetic resonance imaging (MRI) examinations, including diffusion-weighted imaging (DWI; n= 18) and dynamic contrast-enhanced (DCE) MRI ( n= 3). The imaging features of this series were analysed. RESULTS: All lesions appeared as irregular soft-tissue mass lesions located in the middle and posterior margin of the petrous bone. At CT, the normal vestibular aqueduct structure disappeared. Multiple osteoid tissues were present inside the tumour, and destructive bone changes had a "honeycomb" pattern. Twenty cases were accompanied by the incomplete thin bony peripheral rim along the medial margin. On both T1-weighted imaging (WI) and T2WI, all lesions showed hyperintense, hypointense, and isointense mixed signal intensity. Scattered peripheral hyperintensities were found in all cases on T1WI. The mean apparent diffusion coefficient (ADC) value of 18 lesions was (1.35 ± 0.13) × 10 −3 mm 2 /s, which was similar to that of masseter muscles. On enhanced T1WI, all lesions had significant heterogeneous enhancement, and the vascular flowing-void effect was seen in larger lesions (≥1.5 cm). The time–signal intensity curve (TIC) showed a plateau type in all three cases. CONCLUSIONS: The imaging features of ELST, including its location, bone destruction form, MRI signal intensity, and enhancement pattern, are helpful to improve the diagnostic accuracy of this rare tumour. Highlights: Systematic imaging evaluation is critical for diagnosing this rare tumor. This study is different from previous articles reported in the form of case report. Multiparametric functional MR imaging was used to diagnose ELST for the first time. The results of this research can improve the diagnostic accuracy of ELST.